8 Injuries after treatment with mechanical CPR. (26th April 2019) - Milling, Louise; Mikkelsen, Søren; Astrup, Birgitte Schmidt
Abstract : Background: In later years studies concerning injuries as a result of mechanical CPR (mech-CPR) have emerged. A characterization of these injuries could be of importance in a clinical setting, where quick and targeted diagnosis of injuries may prove to be lifesaving. The aim of this study was to characterize potential visceral injuries as a result of mech-CPR. Method: A total of 50 deceased from the Region of Southern Denmark in the years 2014–2018 were included in this retrospective case series. All were autopsied - either in a hospital or forensic setting. Exclusion criteria were trauma, age below 18 years or pregnancy. Results: 38 (76.0%) had injuries. 22 (44%) had the round sternal skin lesions derived from the piston. Visceral injuries were found in 12 cases. 4 had abdominal injuries. Eight patients had thoracic injuries only. The most common visceral injuries were lung contusions and heart contusion. Contrary to previous studies we found 5 injuries to be potentially life-threatening had the patient otherwise survived. All of these patients were <55 years old, had no known prior disease which could explain the injuries and were not in anticoagulant therapy. In one case, a potentially life-saving procedure, Extra-Corporal Membrane Oxygenation, was withheld because of massive haemorrhage. Conclusion: Visceral injuries are not uncommon after mech-CPR. We found lung and heart contusions to be most common. Contrary to what previous studies have described, we found that potentially life-threatening injuries can occur as a result of mech-CPR. Conflict of interest: None to declare. Funding: None to declare.